Protistan community analysis: key findings of a large-scale molecular sampling - Grossmann, Lars (ISME J, 2016)
Protists are perhaps the most lineage-rich of microbial lifeforms, but remain largely unknown. High-throughput sequencing technologies provide opportunities to screen whole habitats in depth and enable detailed comparisons of different habitats to measure, compare and map protistan diversity. Such comparisons are often limited by low sample numbers within single studies and a lack of standardisation between studies. Here, we analysed 232 samples from 10 sampling campaigns using a standardised PCR protocol and bioinformatics pipeline. We show that protistan community patterns are highly consistent within habitat types and geographic regions, provided that sample processing is standardised. Community profiles are only weakly affected by fluctuations of the abundances of the most abundant taxa and, therefore, provide a sound basis for habitat comparison beyond random short-term fluctuations in the community composition. Further, we provide evidence that distribution patterns are not solely resulting from random processes. Distinct habitat types and distinct taxonomic groups are dominated by taxa with distinct distribution patterns that reflect their ecology with respect to dispersal and habitat colonisation. However, there is no systematic shift of the distribution pattern with taxon abundance.